Insetos associados à cultura do urucum, Bixa orellana L.: sua importância relativa e observações bioecológicas sobre Leptoglossus stigmus (herbst) (hemiptera: coreidae), no Ceará. - Rolim, Rita Liduina Alencar (1994)
In Ceará, the annato plant, Bixa orellana L., is associated with a very diversified insect fauna which probably includes species likely to be pests of this crop. In a 3-year study carried out in two experimental plots in Fortaleza and Caucaia, CE, several groups of insects have been observed and collected, showing a predominance of the orders Hemiptera (families Coreidae and Alydidae), Coleoptera (Curculionidae and Buprestidae) and Hymenoptera (Apidae, Anthophoridae and Halictidae). Among the coreids are a most common species, Leptoglossus stigmus (Herbst), found in both areas the year round, and L. gonagra (F.), which occurs in sporadic outbreaks. Both insects feed on green capsules and seeds of annatto. Together with the ligaeid Oxycarenus hyalinipennis (Costa), found in stored annatto seeds, and a defoliating curculionid, Plectrophoroides sp., they apparently make up the insect complex most potentially damaging to the crop, in this region. But additional studies are deemed necessary for a better assessment of these species as annatto pests. B. orellana is also visited by a great number of insect pollinators, particularly hymenopterans, in addition to lepidopterans and dipterans. Among the bees, Apis mellifera L., Trigona spinipes (F.) and Eulaema sp. are particularly common, in addition to various bumble bees, especially the efficient Xylocopa frontalis (Oliv.) and Centris sp. (family Anthophoridae), and the halictid Augochloropsis sp. In general, pollinators in all these groups increase their numbers and activity in the flowering periods (June-July and November-December). A more detailed study on the coreid L. stigmus , an abbundant species and more constantly associated with annatto, showed the following results: 1) the bug customarily sucks green capsules and seeds, which probably affects plant yield, but the economic damage caused by the pest is still difficult to assess; 2) in the field, oviposition usually occurs on the ventral side of the leaf, showing an average of 18 eggs / batch and an eclosion rate around 90%; 3) at a 26°C temperature and 65% relative humidity, the incubation period is about 11 days and development of the 5 nymphal instars takes approximately 4.5, 11.3, 11.2, 12.3 and 17.2 days (1st to 5th instar, respectively); 4) in the field, adult longevity takes about 25 days for males and 21 days for females; 5) L. stigmus nymphs exihibit a marked gregarious behavior, especially the first few days after eclosion, and keep their association with adults as they develop